Sequestration of cAMP response element-binding proteins by transcription factor decoys causes collateral elaboration of regenerating Aplysia motor neuron axons - Dash, Pramod K. (The National Academy of Sciences, 1998)
Axonal injury increases intracellular Ca(2+) and cAMP and has been shown to induce gene expression, which is thought to be a key event for regeneration. Increases in intracellular Ca(2+) and/or cAMP can alter gene expression via activation of a family of transcription factors that bind to and modulate the expression of CRE (Ca(2+)/cAMP response element) sequence-containing genes. We have used Aplysia motor neurons to examine the role of CRE-binding proteins in axonal regeneration after injury. We report that axonal injury increases the binding of proteins to a CRE sequence-containing probe. In addition, Western blot analysis revealed that the level of ApCREB2, a CRE sequence-binding repressor, was enhanced as a result of axonal injury. The sequestration of CRE-binding proteins by microinjection of CRE sequence-containing plasmids enhanced axon collateral formation (both number and length) as compared with control plasmid injections. These findings show that Ca(2+)/cAMP-mediated gene expression via CRE-binding transcription factors participates in the regeneration of motor neuron axons.